Avoiding errors in the diagnosis of polypoidal choroidal vasculopathy in patients with age-related macular degeneration (Part 2: Example cases) (Ukrainian Journal of Ophthalmology, 2025)
Polypoidal choroidal vasculopathy (PCV) is difficult to diagnose subtype of neovascular age-related macular degeneration (nAMD). Although advances in optical coherence tomography (OCT) and OCT angiography (OCTA) have allowed much improved diagnosis of PCV when indocyanine green angiography (ICGA), a gold-standard for diagnosing PCV, is unavailable, the task may still represent a challenge even for the most experienced ophthalmologists. Numerous diagnostic errors (including failure in elicitation or interpretation of symptoms or signs) may be partially due to the absence of a universal algorithm for identification of the pathology. We believe that highlighting the pathological features of importance to confirm diagnosis, and developing a clearly defined sequence of steps for interpretation of OCT and OCTS results will be a valuable approach to improved diagnosis of this type of nAMD. Three nAMD cases that had OCT signs consistent with PCV and required further differential diagnostic assessment to confirm or exclude PCV are presented as examples demonstrating the efficacy of the proposed algorithm. In these example cases, the OCT findings suggestive of PCV are reported, and OCTA segmentation steps with the related actions as per the proposed algorithm are described. The example cases demonstrate that the stepwise assessment of OCT and OCTA results for patients with nAMD allows to determine reliably whether PCV is present or not (i.e., whether the diagnosis should be confirmed or refuted).
Keywords: optical coherence tomography; optical coherence tomography angiography; age-related macular degeneration; polypoidal choroidal vasculopathy; differential diagnosis